A conceptual framework to mitigate the adverse effects of surface urban heat islands through urban acupuncture: a two-phase scenario of diagnosis and prescription at the neighborhood scale - Moussavi A., S. Mohammad Reza; Lak, Azadeh; Tabrizi, Nasibeh (Frontiers in Environmental Science, 2024)
Rising temperaturesIncreasing heat, a major significant global environmental natural challenge, negatively impact has far-reaching adverse effects on health, the environment, society, and the economy. Surface Urban Heat Islands (SUHI), exacerbated by urbanization and climate changes, intensify heighten vulnerabilities for urban areas cities and residents. Urban planning and design have aimed to reduce these vulnerabilities through large-scale and small-scale macro and micro-scale interventions. However, addressing the significance the importance of the capillary effects resulting stemming from small-scale interventions and bottom-up community engagement is importantneeds to be addressed. Urban Acupuncture acupuncture (UA), ) is an emerging approach in contemporary urban planning and design that focuses onwith small-scale interventions, tries to mitigate the effects of SUHIs effects at the community levels. This study aims to develops a framework for reducing mitigating the impacts of SUHIs impacts through UA implementation in urban design. The proposed framework consists of two key phases: diagnosis and prescription. In During the diagnosis phase, we analyzed heat-prone vulnerable areas points to identify indicators contributing to SUHI the development and exacerbation of the SUHIs. Then, we employed the Matrix of Cross Impact Multiplications Applied to a Classification (MICMAC) method technique to comprehensively assess 75 influential indicators related to urban structure across various aspects and scales, focusing on emphasizing the mesoscale. Among them, 30 leading indicators were identified, of which environmental and morphological indicators emerged as significant catalysts in this process. Moving on to the prescription phase, we developed established a UA-based framework called the "5Wh Question", " which addressesing five fundamental questions: why, who, what, how, and where. Our findings can provide comprehensive solutions for policy-makers and urban planners to address mitigate the identified heat-prone vulnerable locationspoints.